Spectrophotometric Estimation of Gliclazide in Pharmaceutical Dosage Forms - Mathrusri Annapurna, M.; Nagoji, K.E.V.; Srinivasa Rao, S.; Patro, S.S. (Asian Journal of Chemistry, 2010)
Three simple and reproducible spectrophotometric methods have been developed for the estimation of gliclazide in pure and its dosage forms by using 0.1 N NaOH (method A), 0.1 N HCl (method B) and pH 7.4 phosphate buffer (method C). The maximum absorbance was observed at 226 nm, 230 nm and 226 nm in methods A, B and C respectively. Beers's law was obeyed in the concentration of 2.5–50 μg/mL, 5–60 μg/mL and 2.5–60 μg/mL in methods A, B and C respectively.